Global Perspectives on Workers' and Labour Organizations (Work, Organization, and Employment, 2018)
This book broadens the research on the underworld of precarious and not-represented workers, through a selection of original case studies from across the globe written by leading experts. The book unveils the working conditions affecting this vast labour force that is so important to capital accumulation in the global age. It also helps us to understand the forms and processes of organization that these groups of workers, almost on an everyday basis, put in place to improve their working conditions and lived experiences.